Tinjauan Sosiologi Hukum Penerapan Sanksi Pelaku Pelanggaran Penanganan Covid-19 di Kota Makassar - Faradillah, Nurafni; Istiqamah; Safriani, Andi (Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims to determine, first how the application of sanctions for people who violate the provisions of the legislation on the regulation of the mayor of Makassar in handling the covid 19 outbreak in Makassar. Second, the extent of the impact caused by the implementation of legislative provisions in handling the Covid 19 outbreak in terms of legal sociology. This research is Library research with research approach using Socio Legal Approach method.The results of this study indicate that the application of sanctions for people who violate the regulations of the mayor of Makassar in handling the Covid 19 outbreak implemented by the Makassar city government has almost completely run effectively, evidenced by the implementation of the justisi operation by the joint TNI-POLRI apparatus where every violator of health protocols is immediately sanctioned at the, penalties fines, as well as administrative sanctions.